BIODEGRADASI METILMERKURI OLEH BAKTERI TANAH YANG DIISOLASI DARI SUNGAI SANGON - Suheryanto, Suheryanto (Program Studi Pengelolaan Lingkungan Program Pascasarjana Universitas Sriwijaya, 2005)
The ability of six bacteria from Sangon River in methylmercury degradation by has been investigated. The aim of this research was to investigate the capability of some bacteria in methylercury degradation and to study their mechanisms. Six isolates were grown in Luria Bertani (LB) media added by methylmercury with the concentration of 2,5 g/mL strain SDM 41 (Enterobacter sp), 2,0g/mL strain SDM 78/9a (Bacillus sp), strain SDPM 8a (Klebsiella sp), strain SDPM 8b (Pseudomonas sp), dan 1,0 g/mL dengan strain SDM 81 (Proteus sp), and strain SDPM 24 (Serratia sp). The cells were incubated at 30o C for 24 hour. After preparation fo biomass, the protein cells were detected by SDS-PAGE Electroforesis. The activity of degradation were determined by measuring the concentration of methylmerkury in media at the initial and the end of growth by using Gas Liquid Chromatography (GLC). The results showed that isolate SDM 78/9a, SDM 81 and SDPM 8have spesific protein with molecular weigth ranging from 18,67-21,32 kDa, and 56,48-64,5 kDa respectively. It is persumable that bacteria have ability in degradation of methylmercury. Furthermore, SDPM 8b and SDM 81 isolate have higher activity in the degradation of methylmercury.